A "crescendo" model: designing food experiences for psychological well-being. (30th July 2021) - Zarantonello, Lia; Grappi, Silvia; Formisano, Marcello; Schmitt, Bernd H.
Abstract : Purpose: This paper aims to advance the design-thinking approach in food from an engineering mind-set toward a positive psychology perspective by investigating how consumer experiences evoked by food-related activities can facilitate, stimulate and enhance individuals' happiness and perceptions of life satisfaction. Design/methodology/approach: A diary field experiment was conducted. Participants from a major European city were asked to reflect on their food-related activities, provide descriptions and answer questions on experiential stimulation derived from these activities in relation to happiness and perceived life satisfaction. Findings: Food-related activities generally result in positive consumer experiences and psychological well-being. Experiential stimulation resulting from food activities is positively related to perceived life satisfaction directly and indirectly via pleasure and meaning. Although the authors found an overall positive relationship between these constructs, they also found differences based on the experience type considered. A "crescendo model" of experiences that details how experiences lead to happiness and perceived life satisfaction is presented. Research limitations/implications: This study is largely exploratory. Future research should adopt an experimental approach and further test the relationship between experiential stimulation, happiness and perceived life satisfaction in the context of food. Practical implications: The paper offers innovation teams in food companies a practical "crescendo model" that can be used to design product–consumer interactions. Originality/value: The research bridges literatures on design thinking, psychological well-being and consumer experiences. By studying the relationship between experiences, happiness and perceived life satisfaction in the context of food, the findings contribute to research on food well-being by expanding the notion of happiness seen only as pleasure. The research also contributes to work on design thinking by offering an experiential framework that contributes to the notion of consumer empathy.